Arthropod biomass carbon stocks across vegetation density gradients in Angke Kapuk Protected Forest, Jakarta, Indonesia - CINDIKIA ANNISA PUSPADEWI; NOOR FARIKHAH HANEDA; CECEP KUSMANA (Society for Indonesian Biodiversity, 2026)
Abstract. Puspadewi CA, Haneda NF, Kusmana C. 2026. Arthropod biomass carbon stocks across vegetation density gradients in Angke Kapuk Protected Forest, Jakarta, Indonesia. Biodiversitas 27 (1): d270128. https://doi.org/10.13057/biodiv/d270128. Blue carbon research has traditionally centered on vegetation and sediment reservoirs, however, the role of faunal components particularly arthropods remain underrepresented. This study examines arthropod community dynamics and their associated carbon stocks across three vegetation density classes in Angke Kapuk Protected Forest, Jakarta, Indonesia. Using a combination of yellow pan traps, light-traps, and manual collection, we estimated arthropod biomass through allometric equations to quantify biological carbon contributions. Our findings show that Diptera (Chironomidae) dominated the assemblages across all densities. Statistical analysis via one-way ANOVA indicated no significant variation in arthropod carbon stocks among the density classes (F2,3 = 0.209, p = 0.822), likely due to high micro-ecological variance at the plot level. However, correlation analysis revealed that carbon stocks were significantly linked to microclimatic stability, showing a strong negative relationship with light intensity (r = -0.84, p<0.05). These results highlight that arthropod carbon distribution in urban mangroves is governed more by localized microclimatic conditions than by broad vegetation density. This study provides a refined perspective on the environmental factors governing small-scale carbon storage and suggests that maintaining structural heterogeneity is essential for sustaining faunal carbon reservoirs in urban mangrove ecosystems.